Photodegradable films based on polyethylene-cassava starch blend using benzophenone/antraquinone or Fe(II) compound as photosensitive agents - Lan, Pham Ngoc; Giang, Nguyen Chau; Thuy, Nguyen Hong (Vietnam Journal of Chemistry, 2014)
This paper is dealing with formulation of photodegradable films based on polyethylene-cassava starch blend using benzophenone/antraquinone or Fe(II) compound as photosensitive compound. Benzophenone, antraquinone and Fe(II) compound were synthesized in the laboratory and characterized by IR and NMR spectra. The films were obtained by extrusion-blowing method and showed good mechanical properties. They were exposed outdoor and indoor for photo-degradability testing. It showed that after four months outdoor their tensile at break decreased 85% and elongation at break about 90%. It is interesting to note that the films keeping 4 months inside the room showed little decrease in mechanical properties. The films are suitable to be used as mulch films and for other purposes. Keyword: Cassava starch, photodegradable film, photosensitizer.